2010
DOI: 10.1007/s11630-010-0416-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various volute designs on volute overall performance

Abstract: This paper discusses the influence of various volute designs on volute overall performance for a certain centrifugal compressor with both vaned and vaneless diffuser. Firstly, based on a free vortex flow pattern and the assumption of a circumferentially uniform flow at the design condition, a corrected method for volute design is adopted.By means of this method, corresponding to five geometric parameters affecting the volute overall performance, ten volute cases are designed. Secondly, the numerical simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…With the increasing popularity of wind tunnel experimental equipment and its ability to provide a wider range of basic information, it is widely used in wind experiments [56,57].…”
Section: Research On Noise Reduction Of Leading-edge Bionic Bladesmentioning
confidence: 99%
“…With the increasing popularity of wind tunnel experimental equipment and its ability to provide a wider range of basic information, it is widely used in wind experiments [56,57].…”
Section: Research On Noise Reduction Of Leading-edge Bionic Bladesmentioning
confidence: 99%
“…Meghnine et al 15 carried out three-dimensional Computational Fluid Dynamics (CFD) simulations for optimizing the design of quasi-rectangular shape of the volute cross sections of one mixed flow turbine. A detailed analysis of the impact of the volute cross-sectional area on performance has been carried out by Qiang et al 16 Their results showed a significant impact of the radial location of the cross-section on volute performance. Morrison et al 17 performed a set of CFD simulations for investigating the effect of the span distribution of the flow angles at the entry of the impeller on the overall performance and loss characteristics of turbocharger turbines for automotive applications.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the design of the components of a centrifugal compressor is an effective method that can be used to improve its performance. Xiaoqing Qiang [1] studied the influence of the volute design on the global performance of the volute, and compared ten kinds of volute design schemes by CFD (computational fluid dynamics) simulation. The final results show that, compared with the forward or symmetrical volute, the backward volute has a more reasonable and uniform velocity field and better comprehensive performance under different working conditions.…”
Section: Introductionmentioning
confidence: 99%